Estimation of HRTFs on the horizontal plane using physical features - Nishino, Takanori; Inoue, Naoya; Takeda, Kazuya; Itakura, Fumitada (Applied acoustics, 2007)
Sound localization can be controlled by using head related transfer functions (HRTFs), which are related to the size of the head, the ears and so on. Since HRTFs are characterized by source directions and subjects, it is necessary to conduct measurements in all directions for all subjects. However, such measurement is expensive and time-consuming. In this paper, we propose a simpler and more useful method that investigates the relationship between HRTFs and physical size by multiple regression analysis. The estimated HRTFs are evaluated by objective and subjective measures. For objective results, the average spectral distortion score is 4.0 dB in a bandwidth ranging from 0 to 8 kHz. Subjective results indicate no significant difference between the measured and the estimated HRTFs in that frequency range. These results support the hypothesis that the proposed method is effective for estimating HRTFs.